Implementasi Penerbitan Akta Kelahiran bagi Anak-Anak Terlantar di Kota Denpasar - Anak Agung Sagung Nandya Pramesti; Ida Ayu Putu Widiati; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2021)
Denpasar City as the capital of Bali Province is currently struggling to overcome the problem of neglected children Data from the Denpasar City Social Service recorded that in 2019 there were 14 orphanages with 470 foster children. The problem raised in this study is to determine legal protection and its impact on neglected children who do not have a birth certificate in Denpasar City For neglected children in Denpasar City to get a birth certificate has a legal basis which is regulated in the applicable laws and regulations in accordance with the provisions governing the birth certificate of neglected children The Department of Population and Civil Registry of Denpasar City has issued birth certificates for all neglected children who are applied for by the orphanage where they live Neglected children who have received a birth certificate will have an impact on their right to identity.